Mortar used for wall whitewash or tile fixing, and preparation method thereof - CAI GUANGYAN; GU DESI; ZHANG XIAOYONG (2017)
The invention belongs to the technical field of mortar used for wall whitewash, and especially discloses a mortar used for wall whitewash or tile fixing, and a preparation method thereof. The mortar is prepared from cement, sand, and glass bead; the granularity of sand, and the glass bead are modified so as to improve the bonding strength of the mortar. The mortar is excellent in workability; no stagging is caused; the mortar is nontoxic, possesses no peculiar smell; bonding is firm; cracking or shedding is not easily caused; and thermal insulation performance is excellent. 本发明涉及粉墙用砂浆技术领域，尤其是种墙体粉刷或贴瓷砖用砂浆及其制备方法，采用水泥、砂子、玻化微珠，并对砂子的粒度，玻化微珠进行改性，使得砂浆的粘结强度得到改善，并且施工性能较优，不下垂、不流挂、无毒、无异味，粘结牢固，不易开裂、脱落，保温性较优。